Preliminary findings on the association between maternal salivary and hair cortisol and the mother-infant-interaction during the early postpartum period - Ernsten, Luisa; Seehagen, Sabine; Nonnenmacher, Nora; Tautz, Juliane; Wolf, Oliver T.; Heil, Martin; Schaal, Nora K. (Psychoneuroendocrinology, 2024)
Maternal capabilities to engage in sensitive caregiving are important for infant development and mother-infant-interaction, however, can be negatively affected by cortisol due to a stress response. Previous research suggested that cortisol possibly impairs cognitive functions important for caregiving behavior, which potentially leads to less maternal sensitivity. However, studies investigating the influence of cortisol using endocrine parameters on the mother-infant-interaction during the early postpartum are lacking. In the current study, fifty-nine mother-infant-dyads participated in a laboratory face-to-face still-face (FFSF) observation when infants were 4 months of age. Maternal and infant positive, negative and matched behavior during the FFSF was microanalytically coded. Cortisol concentrations were obtained using hair and saliva samples. For salivary cortisol, the area under the curve with respect to ground (AUCG) was calculated using two saliva samples obtained after arrival and after the FFSF. Multiple block-wise hierarchical linear regression models were conducted to incorporate potential confounding factors (maternal age, parity, infant gestational age, infant sex) in a first step and, then, test for the association of hair and salivary cortisol with maternal and infant positive, negative and dyadic behavior in a second step. For both it was hypothesized that cortisol assessed in hair and saliva is negatively associated with positive and matched mother-infant-interaction, and positively associated with negative mother-infant-interaction. It could be shown that salivary but not hair cortisol as well as infant gestational age and infant sex related significantly to infant positive and negative affect as well as matched behavior during the reunion phase of the FFSF. Maternal positive affect was unrelated to any of the variables. The results are discussed in regard to the importance of maternal cortisol levels over a longer period of time and more acute situational levels for the mother-infant-interaction as well as the relevance of included confounding factors.